Lipoteichoic acid stimulates the proliferation, migration and cytokine production of adult dental pulp stem cells without affecting osteogenic differentiation. (10th January 2021) - Shayegan, A.; Zucchi, A.; De Swert, K.; Balau, B.; Truyens, C.; Nicaise, C.
Abstract: Aim: To model in vitro the contact between adult dental pulp stem cells (DPSCs) and lipoteichoic acid (LTA), a cell wall component expressed at the surface of most Gram‐positive bacteria. Methodology: Human DPSCs obtained from impacted third molars were cultured and exposed to various concentrations of S. aureus LTA (0.1, 1.0 and 10 µg mL −1 ). The effects of LTA on DPSCs proliferation and apoptosis were investigated by MTT assay and flow cytometry. Mineralization of DPSCs was evaluated by alizarin red staining assay. Migration was investigated by microphotographs of wound‐healing and Transwell migration assays. Reverse transcription polymerase chain reaction was used to examine the effects of LTA on p65 NF‐κB translocation and TLR1, TLR2 or TLR6 regulation. Enzyme‐linked immunosorbent assay was used to investigate LTA‐stimulated DPSCs cytokine production. One‐way or two‐way ANOVA and Tukey post hoc multiple comparison were used for statistical analysis. Results: DPSCs expressed TLR1, TLR2 and TLR6 involved in the recognition of various forms of LTA or lipoproteins. Exposure to LTA did not up‐ or down‐regulate the mRNAs of TLR1, TLR2 or TLR6 whilst LPS acted as a potent inducer of them [TLR1 ( P ≤ 0.05), TLR2 ( P ≤ 0.001) and TLR6 ( P ≤ 0.001)]. Translocation of p65 NF‐κB to the nucleus was detected in LTA‐stimulated cells, but to a lesser extent than LPS‐stimulated DPSCs ( P ≤ 0.001). The viability of cells exposed to LTA was greater than unstimulated cells, which was attributed to an increased proliferation and not to less cell death [LTA 1 μg mL −1 ( P ≤ 0.001) and 10 μg mL −1 ( P ≤ 0.01)]. For specific doses of LTA (1.0 µg mL −1 ), adhesion of DPSCs to collagen matrix was disturbed ( P ≤ 0.05) and cells enhanced their horizontal mobility ( P ≤ 0.001). LTA‐stimulated DPSCs released IL‐6 and IL‐8 in a dose‐dependent manner ( P ≤ 0.0001). At all concentrations investigated, LTA did not influence osteogenic/odontoblastic differentiation. Conclusions: Human DPSCs were able to sense the wall components of Gram‐positive bacteria likely through TLR2 signalling. Consequently, cells modestly proliferated, increased their migratory behaviour and contributed significantly to the local inflammatory response through cytokine release.